Studi Kasus Surat Bunuh Diri Thierry Costa: dalam Perspektif Psikolinguistik Forensik - Josette Rachel Irene Tobing; Bernadus Wahyudi Joko Santoso (Faculty of Humanities, Diponegoro University, 2026)
Suicide notes often become key evidence in forensic investigations. Unraveling the meaning of a suicide note requires a multidisciplinary approach, as it inevitably involves psychological factors, the language used, and the legal implications. So, this study examines Thierry Costa's suicide note from a forensic psycholinguistic perspective. The research focuses on two issues: the disclosure of Costa's psychological state, provoked by the mass media and believed not to correspond to the facts, and the mass media's violation of French law. The purpose of this study is to examine the psychological condition apparent in Costa's suicide note and to explore the legal implications of the provocation by several French media outlets that destroyed Costa's reputation. Data were obtained using the observation method, followed by SBLC (free observation and conversation), and note-taking techniques. The data obtained were then analyzed using qualitative descriptive methods on his suicide note. The results of the study show that the suicide note reflects Costa's psychological condition, characterized by deep emotional distress, despair, and the perception that suicide was his only option. From a linguistic perspective, the lexical choices and sentence structure reveal Costa's psychological condition. Meanwhile, from a forensic legal perspective, the media's reporting of allegations against Costa as a doctor guilty of malpractice has legal consequences under French law, particularly in relation to the provisions on defamation in the Loi du 29 juillet 1881 and the article on provocation au suicide in the Code Pénal. This study confirms that the suicide note not only serves as an expression of Costa's serious psychological problems but also as a case study in the fields of psychology, linguistics, and law.